Penerapan Teori Motivasi dalam Perancangan Aplikasi Edutainment - Halim, Adriani; Soegandi, Andreas (ComTech: Computer, Mathematics and Engineering Applications, 2011)
The purpose of this study was to develop an edutainment application which engages user’s interest like a game application does. The application development implemented motivation theory by Malone and Lepper. The result of this study showed that implementing Malone and Lepper’s motivation theory on edutainment application concerning global warming gives positive result in engaging user’s interest. This application is expected to enhance user’s awareness about global warming.